Electrochemical impedance study on nanofibers of poly(m-anthranilic acid)/polyacrylonitrile blends - Giray, Digdem; Balkan, Timucin; Dietzel, Birgit; Sarac, A. Sezai (Elsevier BV, 2013)
Abstract The nanofibers of poly(m-anthranilic acid) (P3ANA) blends with polyacrylonitrile (PAN) were obtained by electrospinning technique. Electrochemical impedance spectroscopy (EIS) revealed the presence of poly(m-anthranilic acid) in the composite nanofiber structure in addition to the FTIR-ATR spectrophotometric evidences. During the electrospinning P3ANA increased the charge density of polyacrylonitrile solution, and thus, stronger elongation forces were imposed to the jets because of the self-repulsion of the excess charges under the electrical field. This yielded electrospun nanofibers with a substantially straighter shape and smaller diameter. The EIS data were fitted with an equivalent electrical circuit giving a good correlation. SEM analysis of nanofibers showed smaller diameter than for the other nanofibers bearing less ionic groups. Composite bearing carboxylic acid group as a side chains strongly effect the Impedance behavior of nanofibers compared to unsubstituted ones. Poly(m-anthranilic acid) as a charge carriers resulted an important influence on the conductivity of nanofibers. Due to their reactive end groups, nanofibers could be useful for post-polymerization functionalization on the surface.